Changes in abundance of birds in a Neotropical forest fragment over 25 years: a review - Robinson, W. D. (Animal Biodiversity and Conservation, 2001)
Few data are available to evaluate the long term effects of habitat isolation on species richness or abundances in the tropics. Barro Colorado Island (BCI), Panama, has been studied for more than 80 years since its isolation from surrounding lowland forest when the Panama Canal was constructed. Thirty-five percent of the originally present 200 resident species have disappeared. Although the loss of species is well-studied, changes in abundance that might help predict future losses have not been evaluated. One study in 1970 and the present study conducted 25 years later estimated abundances of most bird species on BCI. Comparisons indicate at least 37 species have declined by at least 50%. Twenty-six species of edge habitats are expected to decline as forest maturation proceeds, yet 11 forest species that are now rare may be lost soon. All 26 species that were present in 1970 but not detected in the mid-1990s were rare in 1970. Thus, rarity appears to be a good predictor of extinction risk in this tropical habitat fragment.